Effects of stabilizing materials on soil Cd bioavailability, uptake, transport, and rice growth - Xu, Meizhen; Luo, Fei; Tu, Feng; Rukh, Gul; Ye, Zhengqian; Ruan, Zhongqiang; Liu, Dan (Frontiers in Environmental Science, 2022)
Cadmium (Cd), a widespread toxic heavy metal in farmland soils, is harmful for human health. A field experiment was conducted to investigate the effects of biochar and biochar-based fertilizer on soil pH, organic matter, and available Cd, as well as rice Cd uptake and translocation. The results showed that rice biomass was significantly improved after both application of biochar and high rate of biochar-based fertilizer at tillering stage. The biomass and plant height of rice was improved at filling and maturity stages. Soil pH was significantly increased with the application of biochar but not with the biochar-based fertilizer. The amendments of biochar and biochar-based fertilizer had no significant (p < 0.05) improvement on soil organic matter content. The concentrations of available Cd in soil and the Cd in rice was reduced by 11.94-33.09% with both biochar and biochar-based fertilizer in Ripening. But this effect was much greater under biochar amendment. The lowest bioaccumulation factor (BCF) was due to high concentration of biochar and biochar-based fertilizer. It is concluded that biochar and biochar-based fertilizer in particular at high addition rate are appropriate for decreasing Cd mobility and improve soil quality for contaminated paddy soils.